A Prospective Observational Study on the Efficacy and Safety of Infliximab-Biosimilar (CT-P13) in Patients With Takayasu Arteritis (TAKASIM) - Campochiaro, Corrado; Tomelleri, Alessandro; Sartorelli, Silvia; Sembenini, Camilla; Papa, Maurizio; Fallanca, Federico; Picchio, Maria; Cavalli, Giulio; De Cobelli, Francesco; Baldissera, Elena; Dagna, Lorenzo (Frontiers in Medicine, 2021)
Objectives. Infliximab (IFX) is widely used in patients with refractory Takayasu arteritis (TAK). Recently, the IFX-biosimilar CT-P13 has been introduced for the treatment of inflammatory diseases. The aim of this study was to assess the efficacy and safety of CT-P13 in patients with refractory TAK. Methods. In this prospective, open-label, single-centre trial, TAK patients either already on treatment with IFX-originator (switch group) and never treated with IFX (naïve group) received CT-P13 for 52 weeks. The primary outcomes of the study were: i) number of patients with active disease at month 6; ii) incidence of treatment-emergent adverse events at month 12. Disease activity was assessed at month 6 and month 12 by clinical evaluation (ITAS-2020, ITAS-ESR, and ITAS-CRP scores) and imaging assessment (magnetic resonance angiography [MRA] and [18F]-FDG-PET). Results. 23 patients were recruited (21 switch, 2 naïve). At baseline, 7 patients (32%) were classified as active. At month 6, one patient voluntarily dropped out and 7 patients were still active (30%), including one patient started on a different bDMARD at month 2 due to poor disease control. Mean daily dose of prednisone equivalent was significantly lower than baseline (4.2±1.9 mg versus 4.8±2.1 mg, p=0.009). At month 12, another patient was excluded because of pregnancy desire. Five patients were classified as active (24%), including two patients started on a different bDMARD at month 2 and month 6. Mean daily dose of prednisone equivalent was significantly lower than baseline (3.3±2.6, p = 0.034). No patient experienced side effects during CT-P13 infusion. Overall, one patient experienced grade 1 adverse event and 9 patients experienced grade 2 adverse events. In no case hospitalization was required. CT-P13 retention rate was 90.9% at month 6 and 90.4% at month 12. Conclusion. In this study, the use of IFX-biosimilar CT-P13 in patients with refractory TAK showed a satisfying efficacy and safety profile.